The tourist loyalty index: A new indicator for measuring tourist destination loyalty? - Francisco-José Cossío-Silva; Maria Angeles Revilla Camacho; Manuela Vega Vázquez (Journal of Innovation & Knowledge (JIK), 2019)
The measurement of loyalty is a topic of great interest for the marketing academic literature. The relation that loyalty has with the results of organizations has been tested by numerous studies and the search to retain profitable customers has become a maxim in firm management. Tourist destinations have not remained oblivious to this trend. However, the difficulty involved in measuring the loyalty of a tourist destination is a brake on its adoption by those in charge of destination management. The usefulness of measuring loyalty lies in being able to apply strategies which enable improving it, but that also impact on the enhancement of the organization's results. The study of tourists' loyalty to a destination is considered relevant for the literature and from the point of view of the management of the multiple actors involved in the tourist activity. Based on these considerations, this work proposes a synthetic indictor that allows the simple measurement of the tourist's loyalty. To do so, we used as a starting point Best's (2007) customer loyalty index adapted to the case of tourist destinations. We also employed a variable of results - the tourist's overnight stays in the destination - to create a typology of customers according to their levels of loyalty and the number of their overnight stays. The data were obtained from a survey carried out with 2373 tourists of the city of Seville. In accordance with the results attained, the proposal of the synthetic indicator to measure tourist loyalty is viable, as it is a question of a simple index constructed from easily obtainable data. Furthermore, four groups of tourists have been identified, according to their degree of loyalty and profitability, using the number of overnight stays of the tourists in their visit to the destination. The study's main contribution stems from the possibility of simply measuring loyalty and from establishing four profiles of tourists for which marketing strategies of differentiated relations can be put into practice and that contribute to the improvement of the destination's results.
Keywords: L83; M31; Z30; 650; Customer retention; Destination loyalty; Measurement index; Tourist destination